Effects of extreme environmental exposure conditions on the mechanical behaviour of traditional carpentry joints. (20th July 2019) - Poletti, E.; Vasconcelos, G.; Branco, J.M.; Isopescu, B.
Highlights: Joints govern the behaviour of a timber structures. Weathering of the joint generally caused a degeneration of the joint's performance. Weathered joints with steel plates decreased their capacity by 31%. Abstract: Timber-framed architecture is an important heritage common of many countries. However, this is being lost due to natural decay but also climatic changes and natural hazards. To preserve it, it is important to understand the influence of such actions. Timber joints significantly affect the mechanical performances of timber-framed buildings, being the weakest element. In this paper, results are presented from cyclic pull-out test conducted on traditional timber joints subjected to wind driven rain and flood, both unreinforced and retrofitted, and a comparison is made with those obtained from sound specimens. Wetting-drying cycles mainly influence the stiffness and dissipation capacity.